2022
DOI: 10.3390/cells11152339
|View full text |Cite
|
Sign up to set email alerts
|

MiR-23b Promotes Porcine Preadipocyte Differentiation via SESN3 and ACSL4

Abstract: Genetic improvement of pork quality is one of the hot topics in pig germplasm innovation. Backfat thickness and intramuscular fat content are important indexes of meat quality. MiRNAs are becoming recognized as a crucial regulator of adipose development. Therefore, it is crucial to understand how miR-23b regulates fat metabolism at the molecular level. In the present study, Oil Red O staining, and Western blot were used to evaluate the effect of miR-23b on the differentiation of porcine preadipocytes. Dual-luc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Li et al indicated that miR‐23b ameliorated nonalcoholic steatohepatitis 30 . In addition, our previous study demonstrated that miR‐23b promoted the differentiation of porcine preadipocytes by inhibiting SESN3 expression and promoting ACSL4 expression 19 . The function of miR‐23b is contrary to that of circHOMER1.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Li et al indicated that miR‐23b ameliorated nonalcoholic steatohepatitis 30 . In addition, our previous study demonstrated that miR‐23b promoted the differentiation of porcine preadipocytes by inhibiting SESN3 expression and promoting ACSL4 expression 19 . The function of miR‐23b is contrary to that of circHOMER1.…”
Section: Discussionmentioning
confidence: 89%
“…30 In addition, our previous study demonstrated that miR-23b promoted the differentiation of porcine preadipocytes by inhibiting SESN3 expression and promoting ACSL4 expression. 19 The function of miR-23b is contrary to that of circHO-MER1. In present study, we found that circHOMER1 could directly bind to miR-23b.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations